Driving Innovation in Tourism Workplaces: The Impact of Leadership, Motivation, and Satisfaction on Employee Behavior - Fauzia Septiani; Anah Furyanah; Fadhoilus shof (Journal of Advanced Research in Social Sciences and Humanities, 2024)
Aim: This study examines the effect of transformational leadership, work motivation, and job satisfaction on innovative work behavior. Methodology: The questionnaire was given online using Google Forms and was conducted using a quantitative approach with a sampling technique using accidental sampling. The population in this study was 263, and the sample used was 170 respondents from employees in the hotel sector in Banyumas, Indonesia. This study used SEM-PLS to analyze the data. Findings: The results showed that transformational leadership did not directly affect innovative behavior, but work motivation and job satisfaction affected IWB. Implications/Novel Contribution: Study is unique in methodology and context where studies on innovative work behavior are scarce in similar settings. Innovative work behavior still needs to be considered and improved with satisfaction and motivation elements of job in general and especially in the service sector in Wonosobo, Indonesia. Recommendations are provided along with future directions.